2013
DOI: 10.1210/en.2012-1744
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-375 as a Biomarker of β-Cell Death and Diabetes in Mice

Abstract: Type 1 diabetes is a progressive autoimmune disease that is largely silent in its initial stages. Yet, sensitive methods for detection of β-cell death and prediction and prevention of diabetes are lacking. Micro-RNAs (miRNAs) have been found at high concentrations in body fluids. Here in this study we sought to determine whether an islet enriched miRNA, miR-375, is a suitable blood marker to detect β-cell death and predict diabetes in mice. We measured miR-375 levels by quantitative RT-PCR in plasma samples of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(119 citation statements)
references
References 25 publications
6
109
1
1
Order By: Relevance
“…Potential miRNA biomarkers in T1D Circulating miR-375 levels have been shown to be a biomarker of b-cell death, and were significantly increased at 2 weeks before onset of diabetes in NOD mice, a model of autoimmune diabetes (Erener et al 2013). Elevated expression of miR-326 was found in peripheral blood lymphocytes of T1D patients with ongoing islet autoimmunity (Sebastiani et al 2011).…”
Section: Pkb (Akt) Signaling (Insulin Sensitivity)mentioning
confidence: 99%
“…Potential miRNA biomarkers in T1D Circulating miR-375 levels have been shown to be a biomarker of b-cell death, and were significantly increased at 2 weeks before onset of diabetes in NOD mice, a model of autoimmune diabetes (Erener et al 2013). Elevated expression of miR-326 was found in peripheral blood lymphocytes of T1D patients with ongoing islet autoimmunity (Sebastiani et al 2011).…”
Section: Pkb (Akt) Signaling (Insulin Sensitivity)mentioning
confidence: 99%
“…Their differential expression within tissues has been detected in various disorders, including cancer, cardiovascular disease, and T2D (5). Surprisingly perhaps, stable miRNAs can be found at high concentrations in body fluids and can be readily detected and measured by quantitative PCR (qPCR) using sequence-specific primers (6), making them potentially useful as biomarkers. In particular, circulating miRNA patterns are currently being investigated as potential biomarkers for metabolic diseases and cancers as a means of providing noninvasive, rapid, sensitive, and specific diagnostic measures.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating miR-375 is markedly augmented in STZ-injected mice prior to the occurrence of hyperglycemia or in NOD mice 2 weeks before the onset of diabetes, whereas its levels are decreased 1 week post diabetes. 109 Interestingly, another study showed that the serum miR-375 level was lower in children with newly diagnosed T1D than in the age-matched control individuals. 110 Therefore, we speculated that a sudden increase in circulating miR-375 prior to T1D onset was likely to result from a pool of miR-375 immediately released during the process of β-cell death; in turn, this level will decrease after T1D onset, which may reflect β-cell residual functions.…”
Section: Mirnas: Participants In Autoimmunity-mediated β-Cell Damagementioning
confidence: 99%